HOXC4 homeoprotein efficiently expands human hematopoietic stem cells and triggers similar molecular alterations as HOXB4 - Auvray, C.; Delahaye, A.; Pflumio, F.; Haddad, R.; Amsellem, S.; Miri-Nezhad, A.; Broix, L.; Yacia, A.; Bulle, F.; Fichelson, S.; Vigon, I. (Haematologica (Roma), 2012)
Expansion of hematopoietic stem cells represents an important objective for improving cell and gene therapy protocols. Retroviral transduction of the HoxB4 homeogene in mouse and human hematopoietic stem cells and hematopoietic progenitors is known to promote the cells' expansion. A safer approach consists in transferring homeobox proteins into hematopoietic stem cells taking advantage of the natural ability of homeoproteins to cross cell membranes. Thus, HOXB4 protein transfer is operative for expanding human hematopoietic cells, but such expansion needs to be improved. To that aim, we evaluated the effects of HOXC4, a protein encoded by a HOXB4 paralog gene, by co-culturing HOXC4-producing stromal cells with human CD34(+) hematopoietic cells. Numbers of progenitors and stem cells were assessed by in vitro cloning assays and injection into immuno-deficient mice, respectively. We also looked for activation or inhibition of target downstream gene expression. We show that the HOXC4 homeoprotein expands human hematopoietic immature cells by 3 to 6 times ex vivo and significantly improves the level of in vivo engraftment. Comparative transcriptome analysis of CD34(+) cells subjected or not to HOXB4 or HOXC4 demonstrated that both homeoproteins regulate the same set of genes, some of which encode key hematopoietic factors and signaling molecules. Certain molecules identified herein are factors reported to be involved in stem cell fate or expansion in other models, such as MEF2C, EZH2, DBF4, DHX9, YPEL5 and Pumilio. The present study may help to identify new HOX downstream key factors potentially involved in hematopoietic stem cell expansion or in leukemogenesis.